(untitled) (GAIMS Journal of Medical Sciences, 2025)
Background: Food hygiene and food safety are also major issues worldwide, particularly in developing countries such as India. Significant changes in food production, handling and preparation methods, as well as in the habits of food-eating among people, have made food unsafe. Food handlers are the main contributors to food-borne outbreaks, and food establishments are the main sources of food-borne disease. So, this study assess awareness of personal hygiene and food safety among food handlers in and nearby area of tertiary care hospital. Material and methods: This was an observational analytical cross-sectional study. The study was carried out in surrounding area near tertiary care hospital of Bhuj city and study duration was 3 months. Sample size:193. Results: 36 out of 43 (41.86%) central canteen - mess food handlers, 30 out of 48 (34.88 %) of the restaurants food handlers and 20 out of 98 (23.26%) mobile food handlers had good knowledge of food safety. This study identifies significant gaps in food safety and personal hygiene knowledge among food handlers, particularly among mobile food handlers. Mobile handlers lagged behind in critical hygiene areas such as handwashing, medical check-ups, and food handling practices. Socio-demographic and occupational factors such as younger age, higher education, longer working hours, and possession of food licenses were positively associated with better food safety knowledge.